Spectroscopy Technologies to Screen Peanut Seeds with Superior Vigor Through “Chemical Fingerprinting” - Fonseca de Oliveira, Gustavo Roberto [UNESP]; Hirai, Welinton Yoshio; Ferreira, Dennis Silva; Silva, Karolyne Priscila Oliveira Mota da [UNESP]; Silva, Giovani Chaves [UNESP]; Moraes, Tiago Bueno; Mastrangelo, Clissia Barboza; Pereira, Fabiola Manhas Verbi [UNESP]; Pereira-Filho, Edenir Rodrigues; Amaral da Silva, Edvaldo Aparecido [UNESP] (MDPI, 2024)
Peanut seeds are harvested at different development stages (early and late) due to their uneven maturation. At the time of harvest, approximately 30% of the seeds are still immature, meaning they are not completely filled with compounds (e.g., oil and minerals) and exhibit reduced vigor. Hypothetically, these compounds can be detected as a “chemical fingerprinting” to classify seed maturation stages. Here, we investigated whether non-destructive techniques such as benchtop nuclear magnetic resonance (NMR), laser-induced breakdown spectroscopy (LIBS), and energy-dispersive X-ray fluorescence (ED-XRF) can identify chemical patterns unique to mature seeds with superior vigor. Field-grown seeds were classified into early (R5 and R6) and late (R7, R8, and R9) stages. Seed weight, germination, vigor, H2O2, and MDA (oxidative stress) were analyzed. Oil, potassium (K), and calcium (Ca) were measured digitally using spectroscopy techniques. We found that: (i) oxidative stress and K levels were higher in seeds from the early stages; (ii) seed oil and Ca were proportional to high-vigor seedlings and successful plant establishment in the field; and (iii) the seed chemical composition could be identified autonomously with 87% to 100% accuracy. In conclusion, LIBS, ED-XRF, and NMR technologies can effectively screen peanut seeds with superior vigor through “chemical fingerprinting”.
Keywords: Arachis hypogaeaL; Ca; ED-XRF; K; LIBS; NMR; oil; seed quality